Research on the Indoor Thermal Environment of Industrial Architectural Heritage Based on Human Thermal Comfort—A Case Study in Hefei (China) During Winter - Qiguo Li; Yao Zhang; Chao Wen (Buildings)
With the development of China’s social economy and urbanization, there is a significant stock of urban industrial architectural heritage. Considering the increasing demand for urban land and the renewal of idle sites, the reuse of industrial architectural heritage has become an important measure for urban development, while preserving the city’s industrial memory and the authenticity of architectural heritage. This paper conducts a reuse study on the industrial architectural heritage in Hefei based on human thermal comfort. The motor factory welding workshop and the diesel engine factory cylinder casting workshop in Hefei are selected as research objects. By measuring the physical parameters of the indoor thermal environment and the thermal comfort of human bodies before and after the renovation of these two workshops and by conducting data statistics and regression analyses on the measured data and questionnaire data, an actual mean thermal sensation MTS model of human thermal comfort in the indoor space of the industrial architectural heritage before and after reuse is established. This paper compares the neutral temperature, comfortable temperature range, and duration of thermal comfort at different times for the research objects; analyzes the reasons for the differences in the results; and draws conclusions from the comparative analysis, providing a theoretical basis for the practice of comfortable environment transformation of industrial architectural heritage.